2017
DOI: 10.1007/s00239-017-9809-5
|View full text |Cite
|
Sign up to set email alerts
|

Some Liked It Hot: A Hypothesis Regarding Establishment of the Proto-Mitochondrial Endosymbiont During Eukaryogenesis

Abstract: Eukaryotic cells are characterized by a considerable increase in subcellular compartmentalization when compared to prokaryotes. Most evidence suggests that the earliest eukaryotes consisted of mitochondria derived from an α-proteobacterial ancestor enclosed within an archaeal host cell. However, what benefits the archaeal host and the proto-mitochondrial endosymbiont might have obtained at the beginning of this endosymbiotic relationship remains unclear. In this work, I argue that heat generated by the proto-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 82 publications
0
16
0
Order By: Relevance
“…Mitogenomes are thought to be derived from the common ancestral alpha-proteobacterium though endosymbiosis 71 , 72 . During evolution, most mitochondrial genes have been transferred into the nuclear genome, and this phenomenon was considered with multiple advantages 73 , 74 .…”
Section: Discussionmentioning
confidence: 99%
“…Mitogenomes are thought to be derived from the common ancestral alpha-proteobacterium though endosymbiosis 71 , 72 . During evolution, most mitochondrial genes have been transferred into the nuclear genome, and this phenomenon was considered with multiple advantages 73 , 74 .…”
Section: Discussionmentioning
confidence: 99%
“…For most of the cases, there is an asymmetry between the mutualist partners in many aspects, such as power of control [195] Theory has demonstrated the selective advantage of storing living prey internally for poor times, especially if resource-poor times are sufficiently long and/or frequent [53] Extant alga-protist examples: the metabolite of the photosynthetic symbiont is only provided during daylight; otherwise, the partnership is costly for the host [58] Enabling new niches The host-symbiont association can extend or even enter a new ecological niche where they enjoy reduced competition Aerobic mitochondria could have provided the possibly anaerobic (microaerophilic) host an opportunity to venture into aerobic habitats, while its direct competitors could not. This has happened to a purple protist [202] According to a hypothesis, it was heat generation by mitochondria that allowed the hyperthermophile archaeal host to find cold yet unoccupied niches [203] over the partner, strategic options, availability of alternative partners, etc. [86].…”
Section: Partner Choice Mechanismsmentioning
confidence: 99%
“…The symbiont or the nutrients coerced from it could provide a more stable and balanced diet for the host [ 121 ] Aggregating with cooperative partners is indirectly beneficial as it reduces interactions with non-cooperative individuals [ 200 ] Predatory or parasitic interactions can provide metabolic complementation or acquired resistance against pathogens, that are only beneficial in particular environments Cross-feeding Mutualistic metabolism in which partners depend on metabolic products of each other Removing the product of the partner can be synergistic as it could turn otherwise endergonic reactions to exergonic for the partner [ 42 ]; hence, cross-feeding can be seen as a combination of nutrition and protection (detoxification) benefits The majority of biofilm-forming microorganisms are coupled metabolically due to complementarity and dependency (auxotrophy) [ 42 , 67 , 201 ] Farming A combination of nutrition and protection benefits: the host can feed on the stored stack; the symbiont is protected against environmental fluctuations and predators Typical examples are eukaryotic ciliate - alga symbioses [ 195 ] Theory has demonstrated the selective advantage of storing living prey internally for poor times, especially if resource-poor times are sufficiently long and/or frequent [ 53 ] Extant alga-protist examples: the metabolite of the photosynthetic symbiont is only provided during daylight; otherwise, the partnership is costly for the host [ 58 ] Enabling new niches The host–symbiont association can extend or even enter a new ecological niche where they enjoy reduced competition Aerobic mitochondria could have provided the possibly anaerobic (microaerophilic) host an opportunity to venture into aerobic habitats, while its direct competitors could not. This has happened to a purple protist [ 202 ] According to a hypothesis, it was heat generation by mitochondria that allowed the hyperthermophile archaeal host to find cold yet unoccupied niches [ 203 ] …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to the single-cell scale and cooperation, Dunn 39 suggested that the first step toward eukaryotes arose when an archaeal cell acquired a bacterial symbiont as a source of internal cellular heat. The additional intracellular heat might have allowed thermophilic archaea to migrate to colder environments by a form of endothermy.…”
Section: Heat Flow and Spatial Scalementioning
confidence: 99%